ANALYSIS OF RAINFALL AND TEMPERATURE TRENDS IN DUSTIN MA TOWN, DUTSIN-MA LOCAL GOVERNMENT AREA, KATSINA STATE, NIGERIA - BELLO Y.; LIBERTY F. K. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2022)
The study examined the trend detection of rainfall and temperature in Dutsin-Ma, Dutsin-Ma Local Government Area, Katsina State. The study was aimed at determining the significance of rainfall and temperature trends in the area if it is in accordance with the global climate change scenarios. Secondary data (rainfall and temperature) for thirty-one (31) years from 1984-2014 was used, the data was source from NOAA/NCEP and were subjected to the following analysis; Descriptive statistics, Mann Kendall, Sen’s Slope Model Estimator, Standardized Anomaly Index (SAI), and Rainfall Anomaly Index (RAI). The results revealed a significant decrease of rainfall at (p-value = - 0.0108mm), the values of Kendall Tau, Z- Statistics and Sen’s Slope for rainfall were (-0.3247mm, -2.5495mm and -26.11mm) respectively. There is a significant increase of temperature at (p-value = 0.0037 oC), the values Kendall Tau, Z- Statistics and Sen’s Slope for temperature were (0.3699 oC, 2.9068 oC and 0.0410 oC). The rainfall decrease at the rate of -0.0594-1 (mm) while temperature increase at the rate of 0.0597-1 (oC). There is (52%) of positive anomaly and (48%) of negative anomalies of rainfall while the temperature has (48%) of positive anomaly and (52%) of negative anomalies during the study period. The RAI is (- 3.51mm), which indicates very dry condition and the rainfall pattern changes every decade. The study concluded that there is significant increase in temperature and decrease in rainfall, anomalies of the climatic variable influences, climate variability in the area and Dutsin-Ma is classified as very dry climate and the rainfall pattern changes every decade. The study recommended that human activities which influence increase in temperature should be reduced.